Pelaksanaan perlindungan hukum terhadap anggota multi level marketing PT. Melia Sehat Sejahtera di Pekanbaru ditinjau dari Undang-Undang Nomor 8Tahun 1999 tentang Perlindungan Konsumen - Randu Aditya Rahim; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Literally Multi Level Marketing is marketing carried out through many levels or levels, which are usually known as up line (top level) and down line (lower level). PT Melia Sehat Sejahtera is a multi-level marketing company engaged in the field of health, namely herbal medicine. There are 2 products, namely Melia Propolis and Melia Biyang, in its development there are many consumers who are also members of the PT Melia Sehat Sejahtera MLM network getting inappropriate results as explained by the distributors or Top Leader of PT. Melia Sehat Sejahtera. As for the purpose of this study is First, To find out the implementation of legal protection against members of multi-level marketing PT. Melia Sehat Sejahtera in Pekanbaru is reviewed from Law Number 8 of 1999 concerning Consumer Protection. Second, to find out the responsibilities of Multi Level Marketing Top Leaders at PT. Melia Sehat Sejahtera towards its Downline was reviewed from Law Number 8 of 1999 concerning Consumer Protection.This research is sociological legal research that is research that wants to see the unity between law and society with the gap between das sollen and das sein. This research was conducted in the area of Pekanbaru City precisely by PT. Melia Sehat Sejahtera, while the population and sample are all parties related to the problems examined in this study, the data sources used, primary data, and secondary data, data collection techniques in this study were conducted through interviews, literature review.The conclusions of this study are, First, the form of legal protection for members of PT. MSS Multi Level Marketing has not yet been realized, due to the lack of seriousness of the parties involved, whether from the MLM member PT. MSS, regulations related to business activities Multi Level Marketing is considered not able to provide protection for consumers of Multi Level Marketing. Second, Top Leader Responsibilities do not cover all responsibility for losses obtained by MLM members / members of PT. MSS, Top Leaders Only have moral responsibility as a leader of MLM networks. Because the responsibility for downlines that suffer losses is the responsibility of the business actor, namely PT. MSS as explained in Article 1367 of the Civil Code, Law Number 8 of 1999 concerning consumer protection and Article 2 Letter M of the Minister of Trade of the Republic of Indonesia / M-DAG / PER / 8/2008. The author's advice on the problems studied is First. In order to realize the implementation of the Multi Level Marketing consumer protection of PT. MSS, effective steps from the government, especially to BPSK, are needed to take firm action against Multi Level Marketing businesses that cause losses to the community. Both Governments pay more attention to consumer protection laws because of weak consumer protection. The main factor which is the weakness of consumers is the level of consumer awareness of their rights is still low. This is mainly due to low consumer education. Therefore, the Consumer Protection Act is intended to be a strong legal basis for the government and non-governmental consumer protection institutions to make efforts to empower consumers through guidance and consumer education.Keywords: Legal protection-Multi Level Marketing-Consumers-Top Leaders